2009
DOI: 10.1624/105812409x461199
|View full text |Cite
|
Sign up to set email alerts
|

The Parental Experience of Having an Infant in the Newborn Intensive Care Unit

Abstract: The purpose of this systematic review was to explore and describe the experience of parents with an infant in the newborn intensive care unit (NICU). A literature search covering the period [1998][1999][2000][2001][2002][2003][2004][2005][2006][2007][2008] was conducted. Fourteen articles reporting qualitative studies describing parental experiences and meeting the inclusion criteria were evaluated and themes were identified. Findings revealed that parents with an infant in the NICU experience depression, anxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
276
0
25

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 350 publications
(314 citation statements)
references
References 29 publications
13
276
0
25
Order By: Relevance
“…The key messages that emerged from the survey were the need for consistency in Despite the different set of challenges, many aspects that emerged in our study of perception of HT are consistent with parental perceptions of having a baby admitted in the NICU for other indications [2,3,6,11,14]. Heringhaus et al [10] and Nassef et al [11] identified "emotional landscapes", which included vulnerability, sadness, guilt, feeling that the treatment was not natural, hope, despair, powerlessness, and gratefulness.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…The key messages that emerged from the survey were the need for consistency in Despite the different set of challenges, many aspects that emerged in our study of perception of HT are consistent with parental perceptions of having a baby admitted in the NICU for other indications [2,3,6,11,14]. Heringhaus et al [10] and Nassef et al [11] identified "emotional landscapes", which included vulnerability, sadness, guilt, feeling that the treatment was not natural, hope, despair, powerlessness, and gratefulness.…”
Section: Discussionmentioning
confidence: 65%
“…[1,2,3,4,5,6] Communication is key although it may be suboptimal in the neonatal intensive care unit. [7,8] Hypothermia treatment (HT) has become the standard of care for babies who suffer moderate or severe perinatal hypoxic-ischaemic encephalopathy (HIE) [9] There is very little literature on whether parents are sufficiently informed and how parents experience and perceive this particular treatment.…”
Section: Main Papermentioning
confidence: 99%
“…Sometimes it is necessary to deal with grief in parents after a failed pregnancy or unexpectedly difficult birth and disillusion 4 . Mothers may have a feeling of ambivalence, very often observed as mood swings between hope and hopelessness 5 . The task of neonatal and pediatric departments is to create appropriate conditions not only for children but also for their parents.…”
Section: Intensive Care Unitsmentioning
confidence: 99%
“…Carter et al (2007) suggest that four specific aspects of the NICU experience can exacerbate stress for parents: the physical environment, the baby's physical appearance or behaviour, staff-parent interactions and alterations in the parental role. Giving care to a newborn infant is a fundamental maternal attachment behaviour, and one which is disrupted within the NICU environment (as described by Obeidat et al, 2009). The experience of the NICU parent is often that of being one of many people caring for their child.…”
Section: Introductionmentioning
confidence: 99%